Ovarian enterobiasis: a case report - G. Nair, Geethu; Balan, Prejisha (International Journal of Research in Medical Sciences, 2018)
Enterobius vermicularis (the pinworm) is the most common intestinal nematode in gastrointestinal tract of humans. It commonly infests the lumen of the intestine but on rare occasions has been found in the wall or in the tissues outside the gastrointestinal tract; female genital tract and peritoneum being the commonest sites. It is usually seen as an incidental finding. This is a case of 29-year-old female presented for elective sterilization. A tiny nodule was noted on the surface of ovary during procedure which was sent for histopathological examination. Lesion was composed of necrotic areas and inflammatory cells with cross section of a degenerated worm. The features of the eggs were diagnostic of Enterobius vermicularis. Multiple histologic sections may be required to establish diagnosis in older lesions as in this case.